Intersection of Shahid Bhagat Singh Marg and Horniman Circle - Ghosh, Ayan (2023)
Foundation stone for the buildings around Elphinstone Circle was laid in 1864 by Sir Bartle Frere. The Bombay Gazetteer records, ‘Old Bombay Green was purchased by the Municipality and resold by them at a profit in building lots to English mercantile firms. This gradually transformed the dusty space into an imposing example of street architecture.’